Maternal Factors and Their Relationship with Low Birth Weight: Evidence from a Case-Control Study - Salahin, Kazi Fayzus; El Khairah, Siti Mardiah (Frontiers on Healthcare Research, 2026)
Background: Low birth weight (LBW) remains a major public health concern due to its association with neonatal morbidity and mortality. Maternal factors during pregnancy may influence birth weight outcomes. This study aimed to examine the relationship between maternal factors and low birth weight using a case-control design. Methods: A case-control study was conducted involving 55 mother–infant pairs, consisting of 27 LBW cases and 28 normal birth weight controls. Maternal characteristics, including age, education, employment status, gestational age, pre-pregnancy weight, post-pregnancy weight, hemoglobin levels before and after pregnancy, and infant sex, were collected. The ponderal index was also assessed. Categorical variables were analyzed using appropriate comparative tests, and continuous variables were compared using mean differences. A p-value <0.05 was considered statistically significant. Results: Most mothers were aged 20–35 years (80.0%) and unemployed (76.4%). Nearly half had completed senior high school (49.1%). There were no significant associations between infant sex, maternal age, education, employment status, gestational age, pre-pregnancy weight, post-pregnancy weight, hemoglobin levels before pregnancy, or hemoglobin levels after pregnancy and birth weight outcome (p>0.05). However, the mean ponderal index was significantly lower in the LBW group compared to the normal birth weight group (2.47±0.36 vs. 2.84±0.24; p<0.001). Conclusion: Among the maternal factors examined, only the ponderal index showed a significant association with low birth weight. These findings suggest that neonatal body proportionality may be an important indicator related to birth weight outcomes.